Antiproliferative and pro-apoptotic effects of Andean berry juice (Vaccinium meridionale Swartz) on human colon adenocarcinoma SW480 cells (2017)
ABSTRACT: Vaccium meridionale Swartz, commonly Andean Berry, has a high content of several phytochemicals, such as anthocyanins, phenolic acids, and other flavonoids. However, in spite of its antioxidant capacity, there is little information about its anticarcinogenic properties. This study evaluated the antiproliferative and pro-apoptotic activity of Andean Berry Juice (ABJ) on human colon adenocarcinoma SW480 cells. The antiproliferative activity of ABJ was evaluated on SW480 cells using the Sulphorodamine B assay.The effect on cell viability, cytotoxicity and activation of caspase-3 was analyzed using The ApoTox-GloTM Triplex Assay. Specific apoptotic biomarkers cleaved PARP, total Bcl-2-associated death promote (BAD), phosphorylated BAD, total p53, and phosphorylated p53 were also analyzed. To determine the intracellular redox-state, the Glutathione Assay Kit and 2′-7′- Dichlorodihydrofluorescein diacetate (DCFH-DA) were used, respectively. The antiproliferative assay showed a IC50 value of 8% v/v ABJ, the caspase 3 activity was increased in time-dependent manner in SW480 treated cells, the proapoptotic proteins (cleaved caspase 3, cleaved PARP, P53 and total BAD) were increased by 1.6 to 2.0 fold. In addition, the ABJ-treated SW480 cells increased significantly the production of intracellular reactive oxygen species (ROS), parallel with reduction in the intracellular content of glutathione (GSH) and consequently a decrease of GSH/ oxidized glutathione (GSSG) ratio. In conclusion, the ABJ was able to inhibit SW480 cells proliferation involving apoptotic mechanisms through the perturbation of intracellular oxidative state.